Membilang Awal melalui Numbered Heads Together dalam Permainan Kerang Ajaib Kelompok B - Suprihati Suprihati (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2017)
Children group B TK Dharma Wanita Kuwasen, Jepara mostly in the ability to spell out its initial less than the maximum. This can be seen with words that have not been exact when counting and writing in a spell. The purpose of this research is to know the effect of Numbered Heads Together model in the magic shell game to improve the ability to spell the beginning of Group B of TK Dharma Wanita Kuwasen, Jepara. The research methodology used in this research is quantitative research. The results of research cycle I and the results of research cycle II showed an increase in percentage and completeness. The conclusion of this research is that the application of Numbered Head Together model in magic shell game can improve the beginning of group B TK Dharma Wanita Kuwasen, Jepara